Profile of the motor development in children with overweight - Cruz, Mayara Moura Alves da; Cesario, Stephanie Dornelas; Santos, Caique Aguiar dos; Silva, João Pedro Lucas Neves; Moraes, Íbis Ariana Peña de; Massetti, Thais; Silva, Talita Dias da; Monteiro, Carlos Bandeira de Mello; Prado, Maria Tereza Artero; Pacagnelli, Francis Lopes; et al. (ABCS Health Sciences, 2017)
Introduction: In school-age children, differences in weight and motor skills are still controversial. Objective: To analyze the relation between motor development, level of physical activity, and body mass index (BMI) in children with overweight. Methods: 85 students of both genders, aged 6 to 10 years, living in Presidente Prudente, São Paulo, Brazil, were evaluated. The instruments used were: the classification of BMI/age, the Motor Development Scale and the Modified and Adapted Questionnaire of Level of Physical Activity. The sample was divided into two groups: the overweight group (OWG) was composed of 50 students with nutritional diagnosis of overweight and obesity; the normal weight group (NWG) was composed of 35 eutrophic students. The following tests were used for statistical analysis: Shapiro Wilk (data normality), Student’s t test or Mann-Whitney (independent samples), Spearman’s test (correlation) and χ2 test (proportion), with significance level set at p<0.05. Results: The OWG had significantly lower results for general motor development (91.32±10.68 versus 97.14±9.06; p=0.010), fine motricity (93.21±21.59 versus 103.1±13.12; p=0.0138) and gross motricity (90.31±23.54 versus 112.6±16.07; p=0.0001). A significant positive correlation was found between level of physical activity and motor development in OWG subjects in the domains balance (0.35080; p=0.0125) and spatial organization (0.41820; p=0.0025). Conclusion: When OWG is compared to NWG, results are inferior for general motricity, fine motricity, and gross motricity.